A call for paradigm shift: from competition to cooperation - Krishan, Gopal (2006)
There are many reasons why states will be better off working with each other rather than be in perennial competition. For that to happen we need to develop institutional mechanisms and an appropriate set of incentives. - Reproduced.
Keywords: Federal state relations